Balancing Sino-US Tight Rope : Role of ‘Smart Power’ - Yogaananthan Theva (2019)
The Sino-US rivalry has implications for small states like Singapore. How can the city-state maintain its sovereignty and relevance without being subsumed by the ‘big powers’? The answer could lie in enhancing its ‘smart power’.